O Crasto de Palheiros (Murça) : do calcolítico à idade do ferro - Sanches, Maria de Jesus (Portvgalia : Revista de Arqueologia do Departamento de Ciências e Técnicas do Património da FLUP, 2018)
Excavation work at the site of Crasto de Palheiros (Murça, Vila Real) has started in 1995. A brief outline of the occupation succession (Chalcolithic- Iron Age) is presented here. The importance of the architectural work, occupying 2,5 ha since the Chalcolithic period, justifies a detailed presentation of the different building moments and architectural additions/ alterations : ramparts, paved areas, walls, upright stones.